Role of Adiponectin Receptor 1 in Promoting Nitric Oxide-Mediated Flow-Induced Dilation in the Human Microvasculature - Cohen, Katie E.; Katunaric, Boran; Schulz, Mary E.; SenthilKumar, Gopika; Young, Micaela S.; Mace, James E.; Freed, Julie K. (Frontiers in Pharmacology, 2022)
Chronic administration of exogenous adiponectin restores nitric oxide (NO) as the mediator of flow-induced dilation (FID) in arterioles collected from patients with coronary artery disease (CAD). Here we hypothesize that this effect as well as NO signaling during flow during health relies on activation of Adiponectin Receptor 1 (AdipoR1). We further posit that osmotin, a plant-derived protein and AdipoR1 activator, is capable of eliciting similar effects as adiponectin. Human arterioles (80-200µm) collected from discarded surgical adipose specimens were cannulated, pressurized, and pre-constricted with endothelin-1 (ET-1). Changes in vessel internal diameters were measured during flow using videomicroscopy. Immunofluorescence was utilized to compare expression of AdipoR1 during both health and disease. Administration of exogenous adiponectin failed to restore NO-mediated FID in CAD arterioles treated with siRNA against AdipoR1 (siAdipoR1), compared to vessels treated with negative control siRNA. Osmotin treatment of arterioles from patients with CAD resulted in a partial restoration of NO as the mediator of FID, which was inhibited in arterioles with decreased expression of AdipoR1. Together these data highlight the critical role of AdipoR1 in adiponectin-induced NO signaling during shear. Further, osmotin may serve as a potential therapy to prevent microvascular endothelial dysfunction as well as restore endothelial homeostasis in patients with cardiovascular disease.